Erectile function and health-related quality of life in apparently healthy men - Grönroos, Paavo (My University, 2026)
Background and Objective: Erectile dysfunction (ED) is a common condition affecting both physical and mental health-related quality of life (HRQoL) in men. Studies assessing HRQoL more thoroughly are scarce especially among men without major comorbidities affecting ED and HRQoL. The present study aimed to evaluate the significance of ED on HRQoL among apparently healthy men in primary care setting. Methods: A total of 356 men (age range 45 to 70 years) with cardiovascular risk factors but without manifested diseases were examined. ED was assessed with International Index of Erectile Function (IIEF-5) and HRQoL with the Short-Form Health Survey (SF-36). Adjusted hypothesis of linearity was evaluated using analysis of co-variance (ANCOVA), age was added to the model as covariate. Key Findings and Limitations: Mild ED was detected in 145 (41%) and moderate to severe ED in 60 (17%) men. When adjusted for age, men with moderate/severe ED had lower scores for all dimensions of HRQoL except bodily pain than subjects with no ED. Among those with mild ED, HRQoL was reduced on the general health perception compared to subjects with normal erectile function. Conclusions about causality cannot be made from this cross-sectional study. The study data was collected in 2005–2006 when few men used medicine to treat ED and thus, the impact of ED on HRQoL was probably truly perceived. Conclusions and Clinical Implications: Even apparently healthy middle-aged men may suffer considerably from ED. Physicians should not understate the problem but offer remedy when requested.
Keywords: erectile function, quality of life